Analyzing the effect of physical exercise on social anxiety in college students using the chain mediation model - Hongbo Zhao; Ying Chi; Lei Shi (Scientific Reports)
Abstract This study aimed to explore the relationship between physical exercise and social anxiety among college students and to analyse the chain-mediated role of self-control and mental toughness in it. Using a cross-sectional survey method with physical exercise rating scale, social anxiety scale, self-control scale and mental toughness scale as measurement tools, 534 university students, 50.74% of whom were female and 49.25% of whom were male, were surveyed by stratified whole group convenience sampling method, and mediated effect analyses were conducted using SPSS27.0 and Process plug-in. Two-by-two correlations between physical exercise, self-control, mental toughness, and social anxiety among college students. Physical exercise positively predicted self-control and mental toughness and negatively predicted social anxiety among college students. Self-control and mental toughness individually mediated the relationship between physical exercise and college students’ social anxiety. Self-control and mental toughness acted as chain mediators between Physical exercise and college students’ social anxiety. Physical exercise is an effective way to alleviate social anxiety among college students, both directly on their social anxiety levels and indirectly through the chain-mediated effects of self-control and mental toughness.